Comparison of rat tooth eruption in rats born from diabetic mothers - Salsabila Qotrunnada; Dina Z. Ummah; Mei Syafriadi (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Tooth eruption begins after crown and root formation and may be delayed by gestational diabetes mellitus. Metformin can control blood glucose levels through gluconeogenesis inhibition, and consuming thymoquinone for diabetic treatment will regenerate pancreatic β cells and reduce oxidative stress. Purpose: The objective of this study is to compare the tooth eruption in rats that were born with diabetes and are being treated with either metformin or thymoquinone. Methods: This study used 48 Wistar rats (Rattus norvegicus L.), and the rat sample was divided into four groups, including rats who were born from healthy mothers, rats who were born from untreated diabetic mothers, rats who were born from diabetic mothers that were treated with metformin and rats who were born from diabetic mothers that were treated with thymoquinone. Diabetes was induced by intraperitoneal injection of a single dose of streptozotocin (40 mg/kg BB). Each rat sample was taken with simple random sampling from different mothers, and body weight, blood glucose levels and levels of tooth eruption were recorded. Eruptions of the maxillary right first molar were measured from the cusp of the tooth to the alveolar epithelial lining. Results: Based on the measurements of tooth eruption, it was found that groups A, C and D were closer to mucosa on day 1, 7 and 14 than group B. Based on statistical analysis, there were significant differences (p = 0.03) between group B and groups C and D. Conclusions: Rats born from untreated diabetic mothers have more delays in tooth eruption than those born from diabetic mothers who are treated with metformin and thymoquinone. Thymoquinone has the potential to be an alternative to metformin because it has been shown to be similarly effective.